"You call it a structure taboo!" Relating consultant experiences to changing dynamics in healthcare. Issue 2 (8th April 2019) - van Nistelrooij, Antonie; Homan, Thijs
Abstract : Purpose: The purpose of this paper is to provide a comprehensive reflective perspective on the effects of an intervention in a healthcare organization, as experienced by a consultant. What does a consultant experience when things flounder? Design/methodology/approach: This paper applies a complex responsive process approach as a research perspective and autoethnography as a method to better understand the tensions of a consultant in interacting with members of a client-system. Findings: Focusing on the experiences of the first author during his work as a consultant in a healthcare institution. This approach contributes to the literature by providing a witness, rather than an aboutness, perspective on the experiences of a consultant during a completely unexpected event. Research limitations/implications: This paper is limited by looking at one case in the public sector. It should be considered as exploratory research. Originality/value: The paper can be of value to consultants who are working as a facilitator, as well as to management scholars and practitioners in the field of change management.